Effect of chirality of cysteine on the cell growth and photo-fermentative hydrogen production by using acetate as substrate. (1st April 2021) - Wen, Han-Quan; Ren, Hong-Yu; Xie, Guo-Jun; Xing, De-Feng; Ren, Nan-Qi; Liu, Bing-Feng
Abstract: Cysteine can participate in the essential metabolism of photo-fermentation and plays an important role in biological hydrogen production. However, D-cysteine is usually ignored in current researches despite its potential amounts and unknown effects. This study firstly investigated the photo-fermentative cell growth and hydrogen production with two chiralities of cysteine (L-cysteine and D-cysteine). This and previous studies illustrated proper L-cysteine concentration could improve hydrogen production performance of Rhodopseudomonas sp. nov. strain A7. However, D-cysteine inhibited the cells proliferation and hydrogen production. Groups of initial D-cysteine concentration above 0.3 g/L postponed reactor start-up for several days and obtained little hydrogen production and bacterial biomass. Groups of initial D-cysteine concentration under 0.3 g/L could operate reactor normally in time and obtained about 1000 mL/L hydrogen and 2.0 g/L biomass. Addition time was another key factor, and groups of adding D-cysteine on day 1 influenced little on cells growth but decreased hydrogen production. Other groups with adding time on day 2–5 obtained normal biomass and hydrogen production. Besides, 0.3 g/L functioned as the limit concentration in different initial biomass concentrations for D-cysteine. This work concluded whether the cells could grow and produce hydrogen depended on the addition time and initial D-cysteine concentrations. D-cysteine determined the duration of adapt phase and was regarded as the quorum sensing factor. Furthermore, although biofilm reactors could improve hydrogen production compared to control reactor, biofilm showed little influence on D-cysteine limit concentration. This study would pave the way for the future photo-fermentative hydrogen production.